Efektivitas Pemanfaatan Media E-learning dengan Moodle dalam Menjaga Mutu Pembelajaran Saat Belajar dari Rumah - Ramen Antonov Purba (Jurnal Penjaminan Mutu, 2021)
Education is an effort to gain knowledge, expertise and competence. The journey of education cannot stop. The presence of Covid-19 has resulted in transformations in the education sector. Learning activities have to be done at home. The parameters of each component used in learning activities are expected to produce good results. Thus, the use of e-learning with Moodle. The target is for students to gain knowledge and good results. E-learning with Moodle is an option based on its internet-based work pattern. No place limit and no time limit. A vital evaluation step is carried out. Higher education institutions are required to be professionals. Higher education institutions also face evaluation from LLDIKTI. Internal evaluation is mandatory. All existing elements must be committed to carrying out these obligations. Accommodating agreed targets. Making students understand teaching material. Opening students' insights and thoughts. Students can complete it and get maximum results (sound). The research conducted will look at the effectiveness of using e-learning media with Moodle in maintaining the quality of learning when learning from home. The method used to conduct research is an experiment. The subjects of the Politeknik Unggul LP3M Medan students, the Informatics Management study program are 32 students. Found that the functional level and value accumulation using moodle-based e-learning media with the dynamics of learning from home can maintain and maintain quality. All learning activities go well as expected and targeted.